Efeito da fertilização via solo e foliar com o micronutriente B em cultivares de soja em solos arenosos - Costa, Manoel Antônio Garcez (2025)
The functions performed by the micronutrient boron (B) have a direct impact on the productive potential of plants. Therefore, its proper management through fertilization is a viable and sustainable technology to enhance the productivity of soybean cropping systems in sandy soils. This research project investigated the effect of different B application methods on the yield components of soybean cultivars grown in sandy soil. In a greenhouse setting, three B application methods — no application (control), soil fertilization, and foliar spraying — were tested across five soybean cultivars, totaling fifteen treatments arranged in a completely randomized design with four replications. The plants were grown in pots filled with sandy soil characterized by low available B content. At the end of the crop cycle, the yield components of the soybean plants were evaluated, as well as the B concentrations in the grains and soil. The data were subjected to normality tests and analysis of variance, and when significant, means were compared using Tukey’s test (p < 0.05). In this study, it was observed that B application, following the recommendation of Embrapa Cerrado, did not result in the expected improvements in the evaluated parameters — neither through soil application nor foliar spraying — suggesting a possible toxicity, with few significant differences between treatments. The variation among cultivars may be attributed to their genetic characteristics. The cultivar 64HO114 IPRO showed the highest productivity among the cultivars under the control treatment. We conclude that the response to B application methods varies among cultivars. Further studies are needed to better understand the interaction between application methods and newly developed soybean cultivars.